Dimensional‐Transformation of Ternary‐Alloy through the Manipulation of Reduction Kinetics. (22nd June 2022) - Mahmood, Azhar; He, Dequan; Zhao, Bolin; Talib, Shamraiz Hussain; Cheong, Weng‐Chon; Nan, Zi‐Ang; He, Ying; Han, Dongxue; Wang, Xun; Niu, Li
Abstract: Although significant progress is achieved for the synthesis of noble metal‐based nanocrystals (NCs), the construction of nanostructures with switchable dimensionality is not reported yet. Herein, a facile and general approach for the synthesis of multimetallic (PtCuPb and PtAgPb) NCs with dimensional‐switching properties by manipulating the reduction rate involved in the growth of 2D nanosheets (2D‐NS) and 1D nanowires (1D‐NW) is presented. At a slow reduction rate, PtCuPb and PtAgPb NCs grow to form 2D‐NS, in contrast, at a fast reduction rate, dimensionality alteration occurs to form 1D‐NW. This 2D‐NS to 1D‐NW transition generates compressive surface strain in PtCuPb‐NW with unique intermetallic core, active surface composition and exposes facet to boost oxygen reduction reaction (ORR). In PtCuPb‐NW, compressive strain shifting the d‐band electronic structure of platinum and weakening chemisorption of oxygenated species are shown. In detail, PtCuPb‐NW/C exhibits superior specific and mass activities (4.91 mA cm −2 and 2.65 A mgPt −1 ) for ORR that are ≈19 and ≈15 times higher than the commercial Pt/C. The observations made and chemical principles unveiled in this effort indicate that a general approach exists for dimensional‐switching and show a new class of Pt‐based electrocatalysts with enhanced performance for fuel cells. Abstract : By regulating the reduction rate, the 2D nanosheets (PtCuPb‐NHS) switch to 1D nanowires (PtCuPb‐NW), which generate compressive surface strain in PtCuPb‐NW and enhance oxygen reduction reaction. In detail, PtCuPb‐NW exhibits superior specific and mass activities (4.91 mA cm −2 and 2.65 A mgPt −1 ). After 20 000 cycles of accelerated durability tests, the mass activity and specific activity of PtCuPb‐NW/C loss are of 9.0% and 5.4%.